2012
DOI: 10.1111/j.1465-3362.2012.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Good choices, great future: An applied theatre prevention program to reduce alcohol‐related risky behaviours during Schoolies

Abstract: Introduction and Aims. The contextual and temporal factors of post-school celebratory events ('Schoolies'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Schoolies is synonymous with the consumption of excessive quantities of alcohol 1,2,6,7,10 . This excessive consumption results in alcohol‐related harms for many participants.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Schoolies is synonymous with the consumption of excessive quantities of alcohol 1,2,6,7,10 . This excessive consumption results in alcohol‐related harms for many participants.…”
mentioning
confidence: 99%
“…As a result of these high levels of intake, a large majority experienced at least one adverse outcome such as hangover, vomiting, blackout, or unprotected sex 9 . The heaviest drinkers at Schoolies have been found to be males and those who previously consumed alcohol frequently 2,6,9 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In an 5 attempt to change drinking behaviours during SF on the Gold Coast, Quek et al (2012) investigated the impact of a theatre program aimed at reducing drinking and other risk-taking behaviours during SF. The authors employed diversionary activities but found that these had little or no effect on Schoolies drinking behaviours at this event.…”
mentioning
confidence: 99%